2004
DOI: 10.1523/jneurosci.1972-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Motoneurons Derived from Mouse Embryonic Stem Cells

Abstract: The capacity of embryonic stem (ES) cells to form functional motoneurons (MNs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
190
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(207 citation statements)
references
References 61 publications
(82 reference statements)
16
190
0
1
Order By: Relevance
“…Our own studies on embryonic stem cell-derived motoneurons found that these neurons in many ways resembled motoneurons (Miles et al, 2004;Soundararajan et al, 2006). These cells demonstrated early SFA, yet were found not to have a measurable AHP conductance (Miles et al, 2004).…”
Section: Spike Frequency Adaptationmentioning
confidence: 94%
See 1 more Smart Citation
“…Our own studies on embryonic stem cell-derived motoneurons found that these neurons in many ways resembled motoneurons (Miles et al, 2004;Soundararajan et al, 2006). These cells demonstrated early SFA, yet were found not to have a measurable AHP conductance (Miles et al, 2004).…”
Section: Spike Frequency Adaptationmentioning
confidence: 94%
“…These cells demonstrated early SFA, yet were found not to have a measurable AHP conductance (Miles et al, 2004). This prompted us to study SFA in endogenous mouse motoneurons in spinal slices.…”
Section: Spike Frequency Adaptationmentioning
confidence: 99%
“…The application of both RA and Shh during embryoid body formation in murine ESCs was investigated by Wichterle et al [22], Miles et al [23], Kothapalli and Kamm [24], Brown et al [25], and in human ESCs by Li et al [26], Stacpoole et al [27], and Hu and Zhang [28], among others. Such studies have revealed the synergistic effects of these two factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a weak transient outward K current was recorded in the untreated MSCs, and current significantly increased in differentiated neurons derived from MSCs. From the current-voltage curve, it was possible to determine that transient outward K current was activated at -40 mV with a strong outward rectification, which was similar electrophysiological characteristics of neurons derived from embryonic [32] and neural stem cells [33]. Similar electrophysiology characteristics have been observed in neurons derived from MSCs, although induction procedures were complicated [34] or results were obtained by co-culturing with cerebellar granule neurons [35].…”
Section: Discussionmentioning
confidence: 69%